(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
This paper examines the use of nonverbal linguistic signals on billboard posters during the Covid-19 pandemic in Douala. It has been noticed that nonverbal signals such as sweating, wearing a nose mask, washing of hands with clean running water and soap and standing two metres apart from each other and the use of colours such as white and red among others play an important role in the way human beings communicate especially during a period of crisis. Although it is nonverbal, this means of communication acts more than the verbal one. This work focuses on nonverbal linguistic features used on billboard posters in the city of Douala as a means of creating public awareness in relation to the Covid-19 pandemic so that the contamination and mortality rate can be reduced. This study is of great value because it demonstrates how people should live during a pandemic era without being contaminated. This research uses a qualitative research design. The researcher culled some pictures that were pasted on billboards during the crisis (2020-2021) on the streets of Douala. Insight was drawn from Barthes (1964) theory of semiotics. The findings indicated that people washed their hands with clean running water and soap, they wore masks, arrows were used to show how people should stand with others in public, colours such as red was used to show how dangerous this virus is and the white colour was also used to indicate that people need to be clean during this period so that they can minimise the chances of being contaminated. Capitalisation was used either in red or black to attract the attention of the public to the messages written on the billboards. The researcher concludes that people should develop the culture of reading public notices especially billboard posters during epidemics and pandemics so that they can save their lives.